Health Status of Spiny Lobster Panulirus homarus with Sub-Mersible Net Cage System in the Different Depths at Kepulauan Seribu, DKI Jakarta - Wahjuningrum, Dinamella; Effendi, Irzal; Hadiroseyani, Yani; Budiardi, Tatag; Diatin, Iis; Setiawati, Mia; Puji Hastuti, Yuni; Oman Sudrajat, Agus; Yonvitner; Sri Nuryati; Utami, Putri (Indonesian Society of Scientific Aquaculture (ISSA), 2022)
ABSTRACT Cultivation of Panulirus homarus lobster is now carried out with sub-mersible net cage system at a certain depth in order to obtain optimal temperature, light and water pressure. The purpose of this study was to evaluate the health status of the sand lobster P. homarus which was kept in sub-mersible net cage system measuring 250 cm × 272 cm × 135 cm with a depth of 6 m and 8 m in the waters of Semak Daun Island, Seribu Islands, DKI Jakarta. The average size of lobster seeds used was 93.23 ± 0.99 g/head with a density of 4 lobsters/m2. Lobsters were fed trash fish, molluscs and crustaceans, with a frequency of twice a day at 07.00 WIB 30% and 17.00 WIB 70% of the lobster biomass weight. This study used a completely randomized design with the two depth treatments mentioned above and three replications. Observations of total haemocyte count, differential haemocyte count, phenoloxidase activity, respiratory burst phagocytic activity and histology of lobster hepatopancreas were performed twice every 14 days. Based on the above observations, the depth does not affect the immune response, there is no visible damage to the cells and tissues of the lobster hepatopancreas. Keywords: haemolymph, histology, lobster cultivation, sea, sub-mersible net cage system